Bilateral agreement for academic years 2010/2013 Lifelong Learning Programme (Erasmus) between Università degli Studi di Parma and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme - Subject area: Business studies, management.